Universities and university colleges act (UUCA) 1971 (act30): evaluation from the human rights perspective / Sheba Gumis, Syeela Marlina Uttaman, Wan Khairul Anwar Manan - Gumis, Sheba; Uttaman, Syeela Marlina; Manan, Wan Khairul Anwar (2007)
For the last two semester we have been conducting a research on the University and Universities college Act 1971 (UUCA) in Malaysia. In our research, we concentrated on several sections in the UUCA that are controversial and are expected to infringe the human rights and fundamental liberties of the citizens of Malaysia. The UUCA is a controversial topic of which its abolishment has been repeatedly been called for due to its infringement of human rights and natural justice. The recent call for amendments to the UUCA makes it necessary for a research paper to be done on the UUCA and its infringing provisions. In completing this project paper, we have conducted two interviews with Student Affairs officials from University Teknologi Mara (UiTM) and Universiti Kebangsaan Malaysia (UKM).